National Hospital Discharge Survey, 1987 ([Verlag nicht ermittelbar], 1990)
The 1987 National Hospital Discharge Survey, which is part of a continuing sample of hospital discharge records, supplies medical and demographic information used to calculate statistics on hospital utilization. This survey consists of data abstracted from the face sheets of the medical records for sampled inpatients discharged from a national sample of nonfederal short-stay hospitals. The variables include information on the patient's demographic characteristics (sex, age, date of birth, race, marital status), dates of admission and discharge, status at discharge, diagnoses, procedures performed, source of payment, and hospital characteristics such as number of beds, ownership, and region of the country.